Managing global pollution problems by reduction and adaptation policies - Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper questions the standard results of an international noncooperative reduction game through considering scope effects between reduction and adaptation policies. In particular, it demonstrates that scope effects can result in positively sloped reaction curves. The paper discusses also the role of different conjectures and corner solutions. It concludes that, compared to the well-known standard results, all these effects introduce a good deal of ambiguity surrounding any forecast which is based on purely theoretical grounds.
Keywords: 330; Internationale Umweltpolitik; Umweltschutz; Spieltheorie; Verhandlungstheorie; Theorie